Resolución del caso - Segura, Florencio Pablo; Lucero Zudaire, María Paz; Quiroz, Roberto Carlos; Briggen, Paul; Preisz, Silvana Vanesa; Álvarez Castillo, Joaquín Amadeo (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2024)
-